Use of khakass feldspar in production of ceramic tiles - Shil'tseva A. D. (1999, 1999)
The use of feldspar rock (orthophyre) and feldspar wastes of the Molibden Joint Stock Company (stripping pegmatites and tails resulting from ore concentration) in ceramic mixture compositions is investigated. The dependence of sintering and phase formation on the type and quantity of the feldspar component and the amount of cullet in the mixture is established. A diagram for selection of ceramic mixture compositions with the required sintering degree is developed. The properties and phase composition of tiles with the optimum amount of the feldspar components are studied